Pengaruh Konsumsi Air Kelapa Terhadap Tekanan Darah Pada Pasien Hipertensi - Tarwoto Tarwoto; Mumpuni Mumpuni; Wahyu Widagdo (Quality : Jurnal Kesehatan, 2018)
The provision of high calcium supplements in handling blood pressure is still debated and unclear. This study aims to determine whether the provision of natural drinks high in calcium affects blood pressure in hypertensive patients. The design of this research is quasi-experimental with pre-test post-test one group design. Respondents in this study were 30 elderly people living in Budi Mulia 3 Margaguna Panti Werdha South Jakarta. Inclusion criteria were all elderly with hypertension who received hypertension medication. During the first week for 7 consecutive days blood pressure measurements were taken in the morning. Furthermore, in the second week of the same respondent every day for 7 days, high calcium natural drinks were given, namely 3 x 250 ml of young coconut water given in the morning, afternoon and evening. As long as the intervention of the elderly with hypertension taking the medication is still done. Every day the respondent measured his blood pressure in the morning. The results of the study showed that there was a significant effect of the effect of giving young coconut water to systole and diatole blood pressure (Pv = 0,000, Î± = 0,05). No correlation between BMI and sex with systole and diatole blood pressure in hypertensive patients. There was no correlation between comorbidities and systolic blood pressure (systole Pv = 0.086), but there was a relationship between co-morbidities and diastolic blood pressure (Pv diastole = 0.027). The recommendation of the results of this study is the provision of high-calcium natural drinks (young coconut water) can be applied as nursing interventions for individuals who experience hypertension. Keywords: natural high calcium drinks, young coconut water, hypertension